"Social and Solidarity-based Economy caught between ancestral values and social-ecological transition in the South" - (:unkn) unknown (My University, 2025)
The aim of this article is to highlight the contradiction between the omnipresence of the dynamics of actors in the Social Solidarity Economy (SSE) as a lever for transitions in the South, particularly in Africa and the overseas territories, and their virtual absence in the scientific literature. Although social and solidarity-based economic dynamics are widely present in economic activity in the South, at the theoretical and epistemological level, the SSE in the South constitutes a blind spot in scientific work. This hiatus is all the more surprising given the existence in the South of various forms of social organization akin to SSE structures. Its renaissance was provoked by the neoliberal diktat of the Washington Consensus. To such an extent that it was described as the second largest economy on the African continent in the early 2000s, and recently some have considered it to be the main engine of the African economy in terms of its contribution to employment. Its conceptualization is therefore a major concern. All the more so since, according to the International Labour Organization, the values and principles of the SSE have taken a prominent place in recent legislation on decent work in the South. This shows that it is not necessarily statutes that structure the conceptualization of the SSE. For it is not a question of these structures positioning themselves, according to a mimicry known in other sectors, around the criteria adopted in the countries of the North. In most cases, the driving force behind the SSE is to take over from, or even replace, the failing State, rendered inoperative by the neo-liberal prescriptions of international institutions through structural adjustment plans.
Keywords: African Research